The effects of clay modeling and plastic model dressing techniques on veterinary anatomy training - Burcu ONUK; Ahmet ÇOLAK; Serhat ARSLAN; Sedef Selviler SİZER; Murat KABAK (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2019)
In addition to classical anatomy applications, particularly in medicine education, the contribution of different methods (3D modeling, body painting and clay modeling) has been investigated for the purpose of anatomy training. In recent years, clay modeling which is the one of these methods is frequently used. The aim of the present study was to determine the contribution of clay modeling and plastic model dressing methods to veterinary anatomy training. The ruminant forelimb"s bones, joints, muscles and nerves were chosen as the topic of this study. Clay material was used for bone models, coloured play dough were used for joints, and Colored Eva Sponges were used for muscles and nerves. Students were divided into two groups as new method group and classical method group. The students were given exams and the results of exams were evaluated at the end of each application. It was detected that the student success rate increased when clay modelling and plastic model dressing methods were employed (P<0.05). There was no significant difference for the lesson success rate between male and female students (P>0.05). With this study, the clay modeling and plastic model dressing methods applied for the first time in veterinary anatomy training was found to increase student achievement and motivation significantly. Furthermore, we believe that organ models prepared by this method will contribute to education.